COL10A1 expression is elevated in diverse solid tumor types and is associated with tumor vasculature. (August 2012) - Chapman, Karen B; Prendes, Maria J; Sternberg, Hal; Kidd, Jennifer L; Funk, Walter D; Wagner, Joseph; West, Michael D
Aim: The identification of molecular markers that are upregulated in multiple tumor types could lead to novel diagnostic and therapeutic strategies. The authors screened a panel of RNAs prepared from diverse tumors and tumor cell lines, and compared them with normal tissues and cultured somatic cell types, in order to identify candidate genes expressed in a broad spectrum of tumor types.Materials & methods: Gene expression microarray analysis was carried out on 128 individual tumor samples representing over 20 tumor types, 85 samples representing 31 diverse normal tissue types, 68 tumor cell lines and 97 diverse normal primary cell cultures. Genes were ranked for elevated expression across a large number and variety of tumors relative to normal tissues.Results & conclusion: COL10A1 was identified as a gene with restricted expression in most normal tissues and elevated expression in many diverse tumor types. By contrast, COL10A1 expression was undetectable in the 68 tumor cell lines surveyed in this study. Immunofluorescence studies localized collagen, type X, α-1 (collagen X) staining to tumor vasculature in breast tumors, whereas the vasculature of normal breast tissue was either collagen X-negative or had markedly lower levels. The tumor microenvironment-specific expression of collagen X, together with its localization in the vasculature, may facilitate its use as a novel target for the diagnosis and treatment of diverse solid tumor types.